Neology of Arabic Terms In The Covid19- Pandemic (Morphological Study) - Itsnaini Muslimati Alwi; Nurul Aini (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2021)
This study aims to examine the morphological forms and word-formation processes of Arabic terminology related to the COVID-19 pandemic. Employing a qualitative library research approach, the study analyzes Arabic COVID-19 terms documented in the Dictionary of COVID-19 Terms (English–French–Arabic) published by the Arab League Educational, Cultural and Scientific Organization (ALECSO). The findings reveal that Arabic COVID-19 terminology is realized in two major linguistic forms: words and phrases. Word forms include both nouns and verbs, comprising simple roots as well as derived forms. Phrase forms consist of tarkīb iḍāfī (genitive constructions), verbal phrases, nominal phrases, jar wa majrūr constructions, and tarkīb waṣfī (descriptive constructions). Of the 192 terms analyzed, 46 terms (24%) are single-word forms, while 146 terms (76%) are phrase forms, indicating a clear preference for multi-word expressions in the formation of Arabic COVID-19 terminology. The study also identifies three principal mechanisms of term formation. The first is neology through derivation, which includes maṣdar, ism fāʿil, ism mafʿūl, ism ālah, and ṣīghat al-mubālaghah. The second mechanism is Arabicization (taʿrīb) through the adaptation of foreign lexical items, while the third is translation of foreign terminology into Arabic. Among the derived terms, the analysis identifies 25 maṣdar forms (52%), 5 ism fāʿil forms (10%), 2 ism ālah forms (4%), 1 ṣīghat al-mubālaghah form (2%), and 2 ism mafʿūl forms (4%). In addition, 6 terms (13%) are formed through Arabicization and 7 terms (15%) through translation. These findings demonstrate that Arabic terminology related to the COVID-19 pandemic relies predominantly on derivational morphology while also incorporating borrowing and translation to accommodate newly emerging scientific concepts.